Penerapan Model Pembelajaran Think Pair Share Berbantuan Media Wordwall untuk Meningkatkan Hasil Belajar Siswa Materi Bangun Datar - Salsabilah, Iqriana Nafi'a; Humairah; Susandi, Ari (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
Education has an important role in developing students' potential, one of which is through learning mathematics. Mathematics is not only related to numbers and calculations, but also trains the ability to think logically, critically, and systematically. In elementary school, flat building material is an important basis for understanding geometry concepts. In order for students to easily understand this material, an interesting and effective learning approach is needed. This study aims to improve student learning outcomes through the Think Pair Share (TPS) learning model assisted by wordwall media. This research is a classroom action research (PTK) conducted in two cycles, consisting of planning, implementation, observation, and reflection. The research subjects were students of class IV B SDN 4 Made. Data collection techniques used tests, observation, and documentation. The results showed a significant increase: teacher activity increased from 50% to 89.42%, student activity from 51.14% to 94.32%, and student learning outcomes from 24.14% to 89.66%. Thus, the TPS learning model assisted by Wordwall media was proven effective in improving students' mathematics learning outcomes on the material of flat shapes.